Penerapan Metode Discovery Learning Berbantuan Media Animasi Untuk Meningkatkan Pemahaman Pola Kalimat Bahasa Jepang Kelas XI BBU di SMA Surya Wisata Tahun Ajaran 2023/2024 - Harsana, I Nyoman Ayatma; Yeni, Yeni; Merlyna Yuda Pramesti, Putu Dewi (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 25 No 1 (2025)DO - 10.24843/PJIIB.2025.v25.i01.p11, 2025)
This research aims to (1) improve understanding of Japanese sentence patterns (2) determine students' perceptions of the implementation of Discovery Learning assisted by animation media to improve understanding of Japanese sentence patterns. The research subjects were around 21 students in XI BBU class. The data collection methods used were test methods, observation methods, and questionnaires which were then analyzed using quantitative descriptive methods. The results of the research show that (1) Students' mastery of Japanese vocabulary increases through the application of the Discovery Learning method assisted by animation media. Based on the pre-test results, the average score obtained was 47.4 with a completion percentage of 0%. After implementing Cycle I, the average score obtained by the students increased to 74.1 with a completion percentage of 52.4%. Then after implementing cycle II, the average score obtained by students increased to 86.45 with a completion percentage of 100%. (2) Student responses to the application of Discovery Learning assisted by animation media in Cycle I were classified as positive with an average of 4.25. Meanwhile, cycle II was also classified as positive with an average score of 4.3.